Use of the Indirect Photoluminescence Peak as an Optical Probe of Interface Defectivity in MoS2. Issue 18 (2nd August 2020) - Leonhardt, Alessandra; de la Rosa, César Javier Lockhart; Nuytten, Thomas; Banszerus, Luca; Sergeant, Stefanie; Mootheri, Vivek K.; Taniguchi, Takashi; Watanabe, Kenji; Stampfer, Christoph; Huyghebaert, Cedric; De Gendt, Stefan
Abstract: Defect characterization of 2D materials is a critical aspect for their successful integration in future electronic devices. Here, a simple characterization technique is proposed that opens a path for fast, non‐invasive, quality assessment of transition metal dichalcogenide layers, such as MoS2, and their interfaces. It relates to the correlation between substrate‐induced traps and the indirect‐to‐direct photoluminescence peak ratio. It is shown that the indirect peak is quenched when interfacial trap sites are present. A physical mechanism is proposed to explain the observations based on different recombination mechanisms. Abstract : Indirect‐to‐direct photoluminescence peak ratio: A simple, fast, and non‐invasive method for probing MoS2 material and interface defective trap states.